2020
DOI: 10.26786/1920-7603(2020)573
|View full text |Cite
|
Sign up to set email alerts
|

An Effective and Affordable Camera Trap for Monitoring Flower-visiting Butterflies in Sandhills: with Implications for the Frosted Elfin (Callophrys irus)

Abstract: New advancements in camera trap technology have led to wide-spread use in animal monitoring. In this study we tested whether modern self-contained camera traps could be used to identify small lepidopterans such as the frosted elfin (Callophrys irus). A vast majority of photographed lepidopterans, 76/81 (93.83%), were identifiable to family when moving relatively slowly across the camera’s field of view. Although no C. irus were observed, we were able to identify several species of lepidopterans including those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Numerous technologies are under investigation for monitoring pollinators. For example, camera systems include off-the-shelf digital products such as Apple iPod nanos (Lortie et al 2012), fixed-lens cameras (Steen 2017), camera traps (Mcelveen & Meyer 2020;Naqvi et al 2022), time-lapse cameras (Edwards et al 2015;Smith et al 2021;Alison et al 2022;Nagai et al 2022), and surveillance cameras (Steen & Thorsdatter Orvedal Aase 2011;Mertens et al 2021), as well as recent programmable microcomputers such as NVIDIA Jetson Nano (Bjerge et al 2022), Raspberry Pi (Ratnayake et al 2021(Ratnayake et al , 2023Droissart et al 2021;Bjerge et al 2023), a Luxonis microcomputer-camera capable of edge AI coupled with a Raspberry Pi (Sittinger et al 2023) and nearinfrared sensors, like those offered by FaunaPhotonics (Rydhmer et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous technologies are under investigation for monitoring pollinators. For example, camera systems include off-the-shelf digital products such as Apple iPod nanos (Lortie et al 2012), fixed-lens cameras (Steen 2017), camera traps (Mcelveen & Meyer 2020;Naqvi et al 2022), time-lapse cameras (Edwards et al 2015;Smith et al 2021;Alison et al 2022;Nagai et al 2022), and surveillance cameras (Steen & Thorsdatter Orvedal Aase 2011;Mertens et al 2021), as well as recent programmable microcomputers such as NVIDIA Jetson Nano (Bjerge et al 2022), Raspberry Pi (Ratnayake et al 2021(Ratnayake et al , 2023Droissart et al 2021;Bjerge et al 2023), a Luxonis microcomputer-camera capable of edge AI coupled with a Raspberry Pi (Sittinger et al 2023) and nearinfrared sensors, like those offered by FaunaPhotonics (Rydhmer et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a 2015 review of CT studies, most studies focused on mammals (94.7%), and on carnivores (64.7%) in particular (Burton et al, 2015). Recently, however, researchers have demonstrated the use of CTs to observe insect-plant interactions (Steen, 2017;McElveen and Meyer, 2020;Pegoraro et al, 2020;Naqvi et al, 2022). Naqvi and colleagues showed that both automatic and scheduled recordings significantly outperformed human observers in collecting data on insect pollinator interactions (Naqvi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%